FOMO and Impulse Buying in the Live Streaming Context: The Dual Mediation of E-WoM and Trust - Sari, Novita Kumala; Mus, Abdul Rahman; Laekkeng, Mursalim; Alam, Syamsu; Safar, Ilhan (International Review of Management and Marketing, 2026)
This study examines the psychological and social mechanisms influencing impulsive buying behavior on live-streaming commerce platforms, focusing on the roles of Fear of Missing Out (FOMO), consumer trust, and electronic word-of-mouth (E-WoM). Live commerce is rapidly expanding in Indonesia through platforms such as TikTok Shop and Shopee Live; however, empirical studies in emerging urban markets like Makassar remain limited. Data were collected from 272 respondents with live-streaming purchase experience and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that FOMO positively affects consumer trust, which enhances engagement with E-WoM and drives impulsive buying. Mediation analysis reveals a multi-layer mechanism in which FOMO shapes trust and amplifies the persuasive effect of consumer-generated reviews, supporting the Stimulus–Organism–Response (S-O-R) framework and Social Proof Theory. This study contributes to the literature by introducing a multi-step mediation model and offering new insights into consumer behavior in Makassar as a rapidly growing market. The findings provide strategic implications for marketers and platform developers to optimize scarcity-driven marketing strategies, strengthen trust-building mechanisms, and foster interactive community engagement to improve conversion rates and competitiveness in Indonesia’s evolving e-commerce ecosystem.